2014
DOI: 10.1007/s00586-014-3607-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy versus corpectomy for multilevel cervical spondylotic myelopathy: a meta-analysis

Abstract: As compared with ACCF with plate fixation, ACDF with plate fixation showed no significant differences in terms of postoperative JOA score, fusion rate, but better improved cervical lordosis, lower complication and smaller surgical trauma. As the limitations of small sample and short follow-up in this study, it still could not be identified whether ACDF with plate fixation is more effective and safer than ACCF with plate fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 45 publications
2
42
0
3
Order By: Relevance
“…a Sagittal CT scan and b lateral radiograph of two-level titanium (radiopaque) cage and anterior plate reconstruction following C7-T1 corpectomy. c Sagittal CT scan and d lateral radiograph of two-level PEEK (radiolucent) cage and anterior plate reconstruction following C5-6 vertebrectomy scans in all of the studies would have yielded lower fusion rates, the results are not substantially different than prior reported literature for structural bone grafts and fixed cages [16,24,43,47].…”
Section: Fusionmentioning
confidence: 83%
“…a Sagittal CT scan and b lateral radiograph of two-level titanium (radiopaque) cage and anterior plate reconstruction following C7-T1 corpectomy. c Sagittal CT scan and d lateral radiograph of two-level PEEK (radiolucent) cage and anterior plate reconstruction following C5-6 vertebrectomy scans in all of the studies would have yielded lower fusion rates, the results are not substantially different than prior reported literature for structural bone grafts and fixed cages [16,24,43,47].…”
Section: Fusionmentioning
confidence: 83%
“…The self-assessment NDI scores were obtained from each patient. The neck disability index (NDI) scores were evaluated by categorizing them into the following standard intervals: no disability (0-4), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate (15-24), severe (25-34), and complete disability (> 34). The clinical prognosis was assessed by the NDI scores, which were collected in preoperation and at least 1 year after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Anterior cervical hybrid decompression and fusion (ACHDF) can decompress the anterior cord, reduce the amount of surgical bleeding and maintain the stability of the spinal column [1,2]. Studies have revealed that 3-level anterior cervical discectomy and fusion (ACDF) is associated with a higher incidence of nonunion due to increased graft-host interfaces [3], whereas 2-level ACDF has a higher rate of device-related complications [4,5]. Therefore, combining anterior cervical corpectomy and fusion (ACCF) and ACDF has been introduced as an alternative procedure because it may avoid some drawbacks of traditional fusion techniques [6].…”
Section: Introductionmentioning
confidence: 99%
“…Random-effects models were used depended on the heterogeneity of the studies included. Heterogeneity was analyzed with both the Chi squared test I square test, where p value <0.10 for the Chi squared and I 2 ≥50% implied heterogeneity [16]. The forest plot was a graphic presentation of the analytic result.…”
Section: Methodsmentioning
confidence: 99%